Pembinaan Karakter Siswa Melalui Kegiatan Ekstra Kurikuler Pada MTSN 11 Agam - Sri Hayati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aims to determine the development of student character through extra-curricular activities at MTsN 11 Agam. This research method uses descriptive analysis with a qualitative approach. Extra-curricular activities are really needed in developing student character at MTsN 11 Agam. Through extra-curricular activities, student character, which is not touched in curricular learning activities, can be nurtured and developed to the maximum. Extra-curricular activities carried out at MTsN 11 Agam include: Al Qur'an reading park (TPA), silat, marching training (PBB), dance, volleyball, da'wah, drumband, annisa' forum and scouts. It is hoped that MTsN 11 Agam will further maximize the implementation of existing extra-curricular activities so that student character can also be further developed.